Molecular Pharmacology and Pathology of Strokes - Joen-Rong Sheu (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Stroke, a progressively non-communicable disease, is the second leading cause of death after coronary heart disease in developed countries. The present treatment options for stroke are adapting lifestyle practices, diabetes treatment, drugs, and the management of other factors, but no cure is yet available, despite new insights into molecular and therapeutic targets. Discoveries related to explicating the molecular pharmacology in cerebrovascular function and thrombosis have led to significant advancements in the current treatment paradigm for patients with stroke. Hence, this Special Issue invited scientific papers and reviews from researchers to provide solid evidence from a molecular point of view to scrutinize the molecular pharmacology and pathology of strokes. Platelet activation plays a major role in cardio and cerebrovascular diseases. Platelets also play a key role in the hemostatic process and are associated with various pathological events, such as arterial thrombosis and atherosclerosis. While the currently used anti-platelet drugs such as aspirin and clopidogrel demonstrate efficacy in many patients, they exert undesirable side effects. Therefore, the development of effective therapeutic strategies for the prevention and treatment of thrombotic diseases is a significant priority. Recently, precious metal drugs have conquered the subject of metal-based drugs, and several investigators have moved their attention to the synthesis of various ruthenium (Ru) and iridium (Ir) complexes due to their prospective therapeutic values. We have published this e-book about the "Molecular Pharmacology and Pathology of Strokes" and anticipate that readers will find this book useful regarding the significant challenges and current advances that are presently being made in stroke research, with the possibility of inspiring the application of novel drug development to enrich the devotion and treatment of patients with cardiovascular diseases.